L’Architecte et le programme en situation de concours : une quête de réassurance et d’ouverture - Alexandre Delbos; Jodelle Zetlaoui-Léger (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The research explores the procedural context of French closed competitions in which the program appears as an essential link between defining a commission and designing the work. In this light, a programming agency sought the help of a research laboratory at a school of architecture to understand how architects use this document. What information catches their attention? What conditions do designers feel must be met for the program to stimulate their creativity?This article presents the results of this research partnership based on a qualitative survey conducted in 2019 and 2020 among 16 architects in charge of agencies. Further, it refines the results of research conducted by the laboratory on a national scale, regarding the conduct of competitions during the period 2006-2015. It shows that, beyond the issues of excessively vague or prescriptive commissions, architects seek signs of strong political support for the project, along with prioritized expectations. An emerging need among designers is to understand the foundations of the choices made in order to appreciate their robustness, allowing them to fully embrace the program’s liberties and to be better placed to transcend them. Meanwhile, professionals tasked with writing the program are often encouraged by clients to provide specifications at the competition stage, setting out design solutions without justification and ultimately fostering a sense of mistrust.